2021
DOI: 10.1021/acsmacrolett.1c00722
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Heterogenous Catalysts for Multi-Batch Conjugated Polymer Synthesis via Direct Arylation Polymerization

Abstract: Despite the inherent sustainability direct arylation polymerization (DArP) offers through a C−H activation pathway, the use of expensive homogeneous Pd catalysts remains problematic for large-scale conjugated polymer (CP) synthesis. Herein, the first report on the recycling of heterogeneous catalysts for CP synthesis using DArP is presented. We found SiliaCat Pd-DPP to be a highly efficient and recyclable catalyst for multi-batch CP synthesis providing CPs with molecular weights (M n ) up to 82 kg/ mol even af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…We noted that the batch reaction was performed under ideal reaction conditions (5 mol% Pd/C with a monomer concentration of 0.03 M) as reported. 34–37 Both reactions were conducted three times, and we demonstrated the high reproducibility of molecular weight and Đ with very small errors between runs (9.8% for M n and 15.5% for Đ ) using our flow system (Table 1), compared to much larger errors in batch synthesis (24.1% for M n and 13.4% for Đ ) (Table S2†). In the flow reaction, the resulting PTB7 exhibited an average M n of 8.2 kDa and a broad Đ of 3.29 with two distinct peaks in GPC traces.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…We noted that the batch reaction was performed under ideal reaction conditions (5 mol% Pd/C with a monomer concentration of 0.03 M) as reported. 34–37 Both reactions were conducted three times, and we demonstrated the high reproducibility of molecular weight and Đ with very small errors between runs (9.8% for M n and 15.5% for Đ ) using our flow system (Table 1), compared to much larger errors in batch synthesis (24.1% for M n and 13.4% for Đ ) (Table S2†). In the flow reaction, the resulting PTB7 exhibited an average M n of 8.2 kDa and a broad Đ of 3.29 with two distinct peaks in GPC traces.…”
Section: Resultsmentioning
confidence: 85%
“…[21][22][23][24] Using a heterogeneous catalyst is attractive as the catalyst is easily separable from the product, meaning that no additional purification processes are required, and it is easy to handle with high air stability and cost-effectiveness. [25][26][27][28][29][30][31][32][33][34][35][36][37] In the field of organic semiconductors, Pd catalyzed cross-coupling reactions, including the Stille, Suzuki-Myaura, and Heck couplings, have been successfully conducted for small molecule synthesis and reported with high yields. For conjugated polymer synthesis, few studies have been reported as well and they have clearly demonstrated the benefits of having a high purity polymer product with a low Pd residue when a heterogeneous catalyst was used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In late 2021, Thompson and co-workers reported that SiliaCat DPP-Pd can be successfully employed in the direct arylation polymerization for the large-scale and green synthesis organic semiconducting polymers. 1 The catalyst, an ORMOSIL functionalized with diphenylphosphine ligands bound to Pd(II) in which every Si atom is bound to the C atom of a methyl group, 17 was found to be highly efficient and recyclable affording polymers with molecular weights up to 82,000 g/mol.…”
Section: Polymeric Arylationsmentioning
confidence: 99%
“…The investigations are mainly focused on the DArP of different C–H monomers and can be classified into two categories. One is applying well-known aromatic units in the construction of CPs, for example, 2,2′-bithiophene (BT), thieno­[3,4- c ]­pyrrole-4,6-dione (TPD), , and 3,4-dioxythiophene (DOT), , as C–H monomers, and the DArP conditions are optimized to yield CPs with higher molecular weights, ,,, less structural defects, ,,,, and better sustainability. ,,,, The other is designing new C–H monomers to attain high DArP activity and CPs with promising optoelectronic properties simultaneously. β-Halogenated thiophene derivatives are typical examples of this type of C–H monomers. ,, The introduction of halogen atoms at ...…”
Section: Introductionmentioning
confidence: 99%